2016
DOI: 10.4317/jced.52811
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of droplet and airborne isolation precautions among dental health professionals during the outbreak of corona virus infection in Riyadh city, Saudi Arabia

Abstract: BackgroundThis study aimed to determine knowledge, attitude and practice of airborne and droplet isolation precautions among Dental Health Professionals (DHPs) (dental students, interns, practitioners and auxiliaries) during the outbreak of MERS (Middle East Respiratory Syndrome), corona virus infection in Riyadh city, Saudi Arabia. Material and Methods A cross-sectional survey was conducted among 406 dental health professionals (DHPs) working in selected dental facilities in Riyadh city, Saudi Arabia during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
38
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 17 publications
13
38
2
Order By: Relevance
“…Possible explanation for these findings could be the knowledge gap and poor understanding of disease transmission via high aerosol production during dental procedures. These results are comparable to some of the studies which concluded that dentists' knowledge of respiratory disease contagion and its management was less as compared to other healthcare providers [27], despite their proximity to the patient during treatment [28]. Likewise, in a study conducted in Qassim in perspective of MERS, majority of health workers (57.6%) replied incorrectly when asked whether antibiotics are first choice drugs [21].…”
Section: Resultssupporting
confidence: 77%
“…Possible explanation for these findings could be the knowledge gap and poor understanding of disease transmission via high aerosol production during dental procedures. These results are comparable to some of the studies which concluded that dentists' knowledge of respiratory disease contagion and its management was less as compared to other healthcare providers [27], despite their proximity to the patient during treatment [28]. Likewise, in a study conducted in Qassim in perspective of MERS, majority of health workers (57.6%) replied incorrectly when asked whether antibiotics are first choice drugs [21].…”
Section: Resultssupporting
confidence: 77%
“…This result was in consistent with the previous studies in other parts of Saudi Arabia which indicated that general Saudi population, health care worker as well as medical students showed a high level of awareness in the clinical aspect of the disease. 11,12,18,19 This awareness could be attributed to the awareness campaigns in the hospital and on social media, which were the most common sources of information. As recommended by CDC, Saudi Arabia has led the relevant authorities to initiate educational campaign targeted towards public and health professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Sociodemographic factors which were commonly associated with better health literacy included higher educational level (23, 26, 27, 33, 34, 36, 37, 39, 40, 42, 43, 45, 72-77, 80-82, 88, 89), increased age (23,26,30,37,40,43,48,50,63,65,72,74,75,78,84,85) and female gender (13,16,23,26,33,34,38,40,41,44,45,60,62,72,74,78,80,81,84,85,89). For health systems-based factors, increased experience in the healthcare system (48,56,63,76,77,89) and attendance in health education programs (28,33,58,60,71,<...>…”
Section: Determinants Of Health Literacymentioning
confidence: 99%